2009
DOI: 10.1152/japplphysiol.91245.2008
|View full text |Cite
|
Sign up to set email alerts
|

Aging and muscle fiber type alter K+ channel contributions to the myogenic response in skeletal muscle arterioles

Abstract: Kang LS, Kim SJ, Dominguez JM 2nd, Sindler AL, Dick GM, Muller-Delp JM. Aging and muscle fiber type alter K ϩ channel contributions to the myogenic response in skeletal muscle arterioles. J Appl Physiol 107: 389 -398, 2009. First published April 30, 2009 doi:10.1152/japplphysiol.91245.2008.-Aging diminishes myogenic tone in arterioles from skeletal muscle. Recent evidence indicates that both large-conductance Ca 2ϩ -activated (BKCa) and voltage-dependent (K V) K ϩ channels mediate negative feedback control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 46 publications
8
47
3
Order By: Relevance
“…6B) suggest that BK Ca channels do not play a key role in functional maladaptation of aged cerebral arteries to high pressure. Previous studies reported that with advanced age the activity of K V channels may increase in skeletal muscle arteries (32) and that disruption of K V channel function may contribute to the adaptation of young rat cerebral arteries to hypertension (4). Yet data obtained with inhibitors of K V channels (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…6B) suggest that BK Ca channels do not play a key role in functional maladaptation of aged cerebral arteries to high pressure. Previous studies reported that with advanced age the activity of K V channels may increase in skeletal muscle arteries (32) and that disruption of K V channel function may contribute to the adaptation of young rat cerebral arteries to hypertension (4). Yet data obtained with inhibitors of K V channels (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Role of BK Ca channels in regulation of pressure-induced SMC calcium signaling and myogenic constriction in MCAs. Regulation of large-conductance Ca 2ϩ -activated K ϩ (BK Ca ) channel activity represents an important mechanism modulating the magnitude of pressure-induced myogenic constriction (32,52). To assess the role of BK Ca channels in functional maladaptation of cerebral arteries to hypertension in aging, we tested the effect of iberiotoxin on myogenic constriction (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is associated with a reduction in BK Ca channel expression and function in rat coronary and skeletal muscle arteries, 63,64 and this might alter conducted vasomotor responses in arterioles from aged individuals. In hypertensive animals, cerebral artery BK Ca channels are upregulated, 65 whereas in diabetic mice and rats the b 1 -subunit of the BK Ca channel is downregulated, leading to impaired function of the channel.…”
Section: 58mentioning
confidence: 99%
“…Abnormal Src kinase phosphorylation of hK v 1.5 channels is implicated in familial atrial fibrillation (Yang et al, 2010). In addition, K v 1.5 current plays a role in the maintenance of the cell membrane potential in a wide variety of cells/tissues, such as pancreatic beta cells (MacDonald and Wheeler, 2003), brain tissue (Tipparaju et al, 2012), macrophages (Vicente et al, 2006) and skeletal muscle (Kang et al, 2009), as well as smooth muscles in vessels (Overturf et al, 1994) and airways (Adda et al, 1996). Therefore, tyrosine phosphorylation of hK v 1.5 channels could also be important in maintaining normal cellular function of these types of cells.…”
Section: Discussionmentioning
confidence: 99%